SISTEM INFORMASI MITIGASI BENCANA TSUNAMI DI SEKITAR SARANA DAN PRASARANA PERIKANAN PADA PELABUHAN SAMUDERA CILACAP - , Titik Rahayuningsih ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Indonesia is an archipelagic state of the world where three plates meet, they are the Indo-Australian Plate, the Eurasian Plate and the Pacific plate. Cilacap Regency is one of the areas having high risk of tsunami hazard in Indonesia. When a large tsunami occurres in Cilacap and its surrounding areas, it will bring a severe impact to inhabited areas along the coast with high density population. Many key development areas of Cilacap, especially the oil industry is located directly overlooking the Indian Ocean coastline. Under the seabed of the Indian Ocean, several hundred kilometers south of Cilacap, lies one of the main zones of collision of tectonic plates of the earth, which is the main source of earthquakes cause tsunamis. There are some aspects as the background of how importance to build an information system of the Tsunami disaster mitigation, in the area of fisheries infrastructure and facilities at the port of Cilacap ocean. The first aspect is because of unsufficient society knowledge about the tsunami. The second is lack of information of the society in reducing the impact of the tsunami disaster in the future. The third aspect is the delivering information about tsunami was done manually, such as distributing pamphlets and books. This research aims to design an information system Web-based Tsunami disaster mitigation, start from the planning phase to implementation phase. In order to facilitate users in accessing information about the tsunami mitigation in this study, the authors will perform data analysis Tsunami with the output of all things information about the Tsunami that will be integrated with internet technology applications Google Maps API on the tsunami evacuation route.